MODELLING OF BIOMASS GASIFICATION FOR HYDROGEN PRODUCTION USING COMPUTATIONAL FLUID DYNAMICS (CFD) - MOHD TAMIDI, ATHIRAH (2011)
Biomass steam gasification process has emerged as a clean and efficient way of producing H2. However, experimental study of biomass gasification is costly and dangerous to human being. Simulation and modelling approach is expected to be more cost saving, safe and easy to scale up in order to study the biomass gasification process. In this work, computational fluid dynamic (CFD) approach using the commercial CFD software, ANSYS Fluent® V6.3 has been utilized in order to study the hydrodynamics and the gasification reactions in the fluidized bed gasifier. The overall research objective of this work is to obtain the optimum condition for biomass steam gasification process. For this, a hydrodynamics and a steady state reaction models were developed and validated with literature data. The hydrodynamics model was developed in order study the effect of steam inlet velocity, solid particle size and bed height to diameter ratio to the solid fluidization in the fluidized bed gasifier using Eulerian-Eulerian multiphase model coupled with kinetic theory granular flow approach. The reaction model was developed using volumetric reaction model approach in order to predict the H2 production from the gasifier. The reaction model was used to predict the effect of reaction parameters such as gasification temperature, steam to biomass ratio and adsorbent to biomass ratio to the production of H2 from biomass gasification process. The findings from the developed hydrodynamics and reaction model were compared with experimental and simulation data from literature and were found to be in good agreement.